Religious Motivated Hate Crimes: Reporting to Law Enforcement and Case Outcomes - Walfield, Scott M. (American journal of criminal justice, 2017)
Relative to non-bias motivated crimes, hate crimes have much graver consequences for victims and their community. Despite the large increase in religious hate crimes over the past decade relative to all other hate crime, little is known about these types of crimes and the factors associated with both reporting to law enforcement and case outcomes. Utilizing the National Crime Victimization Survey and National Incident-Based Reporting System datasets, this study examines the relationship between victim, offender, and incident characteristics on reporting to law enforcement and case outcomes. Most religious hate crimes are not reported (41.3 %) in part due to perceptions of law enforcement’s perceived response. Of the violent incidents that are reported, the vast majority do not result in the arrest of an offender (22.2 %). Whereas only a small number of variables related to the seriousness of the offense are associated with both reporting and arrest, these exhibited large effect sizes.